Inheritance and Development of Chinese Kang in Interior Space - Yang, Long; Zakaria, Safial Aqbar (UI Scholars Hub, 2024)
The Chinese kang is an ancient technology that combines an integrated household system for cooking, sleeping, and heating. Most of the existing research focuses on the energy performance of Chinese kang and its impact on the interior environment and tries to adapt it to the modern interior space through the improvement of its technology. However, if we only focus on the research and improvement of the technical level of Chinese kang, it is not conducive to the effective inheritance and development of the culture. This paper studies the concept of 'inheritance and development' of Chinese kang culture more comprehensively from the perspective of interior design. The study proves that Chinese kang is not only a survival necessity to cope with cold, but also an expression of people's emotional catharsis and psychological needs, and that the intangible values of Chinese kang culture can be integrated into tangible modern living spaces and developed in the process of modernisation. The results of the study can be used as a starting point for enriching the Chinese kang culture and interior living culture from different perspectives in the future.